Pengaruh Konsentrasi Zat Pengatur Tumbuh NAA dan Jenis Pupuk Organik Terhadap Hasil Tanaman Serai Wangi (Cymbopogon nardus L.) - ARAT, I GEDE NADI; WIRAATMAJA, I WAYAN; KARTINI, NI LUH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Effect of Concentration of Growth Regulating Substances NAA and Types of Organic Fertilizer on  Yield of Citronella  ( Cymbopogon nardus  L.) Citronella is widely used in the therapeutic scrub and aromatherapy industry, especially in the Province of Bali. The aromatic oil produced from the citronella plant is used for incense or aromatic candles. The purpose of the study was to determine the effect of growth regulators NAA ( Naphthalene acetic acid ) and types of organic fertilizers on the yield of citronella plants. The treatment used consisted of two factors: the concentration of the NAA auxin hormone with the concentration of A 0  = 0 ppm, A 1  = 10 ppm, and A 2  = 20 ppm as the first factor. The second factor is the type of fertilizer P 0  = soil, P 1 = vermicompost 50 g and P 2  = 100 g fertilizer goat manure. The results showed the interaction between the concentration of auxin NAA with the type of organic fertilizer significantly affected the number of leaves, number of tillers, and the roots fresh weight. Combination treatment A 1 P 2  (10 ppm NAA and 100 g fertilizer goat manure) showed the highest leaf number (64.07), the highest number of tillers (11.29) and the highest fresh weight of roots (44.17 g), compared with A 2 P 1  and A 1 P 0  with the lowest values ??of 7.16, 41.47, and 25.4 g, respectively. NAA auxin treatment singly significant effect on leaf area and fresh weight leaf. NAA concentration of 10 ppm (A 1 ) provides the highest leaf area (70.09 cm 2 ) and fresh root weight (47.77 g), compared to control (A 0 ) with the lowest value of 65.85 cm 2  and 33.38 g. Organic fertilizer treatment significantly affected the fresh weight total and dry weight total. Fertilizer goat manure 100 g (P 2 ) produce a total crop fresh weight of 147.57 g and dry weight of 64.28 g, compared to treatment with P 0  and P 1  with the lowest values 108.43 g and 49.99 g, respectively.